2015
DOI: 10.1136/archdischild-2014-306886
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of children with hereditary tyrosinaemia following newborn screening

Abstract: Universal NBS for HT1 should be introduced in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
80
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 21 publications
7
80
3
1
Order By: Relevance
“…33 Medium-term followup results of the effect of nitisinone treatment on clinical course of HT1 revealed that none of the patients treated from the neonatal period developed detectable liver disease. 44 In sharp contrast, all late-treated HT1 patients had chronic liver abnormalities before receiving nitisinone and developed cirrhosis, and some developed HCC. 23,44,63,68 Larochelle et al reported that LT was performed in 71% of non-nitisinone treated patients and 26% of late-treated patients.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…33 Medium-term followup results of the effect of nitisinone treatment on clinical course of HT1 revealed that none of the patients treated from the neonatal period developed detectable liver disease. 44 In sharp contrast, all late-treated HT1 patients had chronic liver abnormalities before receiving nitisinone and developed cirrhosis, and some developed HCC. 23,44,63,68 Larochelle et al reported that LT was performed in 71% of non-nitisinone treated patients and 26% of late-treated patients.…”
mentioning
confidence: 99%
“…35,67 Early treatment has been shown to decrease the risk of HCC. 44,46,56 The earlier the nitisinone treatment is commenced, the lower the risk a patient should develop HCC as the exposure of the liver to the mutagenic effects of FAA and MA is lowered. 33 Medium-term followup results of the effect of nitisinone treatment on clinical course of HT1 revealed that none of the patients treated from the neonatal period developed detectable liver disease.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemically, patients typically have hypertyrosinemia and toxic metabolites. Toxic metabolites and their derivates such as fumarylacetoacetate (FAA), maleylacetoacetate, succynylacetoacetate (SA) and SA playa major role in tissue damage with hepatic, renal and neurological findings (2). The FAH gene is mapped in human chromosome 15q (15q23-25) and consists of 14 exons spanning over 35 kb of DNA.…”
Section: Introductionmentioning
confidence: 99%